ANTEC 2006 plastics annual technical conference proceedings. (Society of Plastics Engineers, 2006)
The latest developments in plastics, includes all of the 100+ sessions, covering over 700 presentations by plastics experts.
Keywords: Plastics -- Congresses.; Plastics industry and trade -- Congresses.; elektronické knihy; electronic books